Atomic carbon [C i](3P1–3P0) mapping of the nearby galaxy M 83. (12th April 2021) - Miyamoto, Yusuke; Yasuda, Atsushi; Watanabe, Yoshimasa; Seta, Masumichi; Kuno, Nario; Salak, Dragan; Ishii, Shun; Nagai, Makoto; Nakai, Naomasa
Abstract: Atomic carbon (C i ) has been proposed to be a global tracer of the molecular gas as a substitute for CO, however, its utility remains unproven. To evaluate the suitability of C i as the tracer, we performed [C i ]( 3 P 1 – 3 P 0 ) [hereinafter [C i ](1–0)] mapping observations of the northern part of the nearby spiral galaxy M 83 with the Atacama Submillimeter Telescope Experiment (ASTE) telescope and compared the distributions of [C i ](1–0) with CO lines [CO(1–0), CO(3–2), and 13 CO(1–0)], H i, and infrared (IR) emission (70, 160, and 250 μm). The [C i ](1–0) distribution in the central region is similar to that of the CO lines, whereas [C i ](1–0) in the arm region is distributed outside the CO. We examined the dust temperature, T dust, and dust mass surface density, Σdust, by fitting the IR continuum-spectrum distribution with a single-temperature modified blackbody. The distribution of Σdust shows a much better consistency with the integrated intensity of CO(1–0) than with that of [C i ](1–0), indicating that CO(1–0) is a good tracer of the cold molecular gas. The spatial distribution of the [C i ] excitation temperature, T ex, was examined using the intensity ratio of the two [C i ] transitions. An appropriate T ex at the central, bar, arm, and inter-arm regions yields a constant [C]$/$ [H2 ] abundance ratio of ∼7 × 10 −5 within a range of 0.1 dex in all regions. We successfully detected weak [C i ](1–0) emission, even in the inter-arm region, in addition to the central, arm, and bar regions, using spectral stacking analysis. The stacked intensity of [C i ](1–0) is found to be strongly correlated with T dust . Our results indicate that the atomic carbon is a photodissociation product of CO, and consequently, compared to CO(1–0), [C i ](1–0) is less reliable in tracing the bulk of "cold" molecular gas in the galactic disk.